Studies on Pollen Storage Conditions and Period on Seed Yield and Quality of Sunflower (Helianthus annuus L.) Hybrid KBSH-1 - SALMA SULTANA; S. RAJENDRA PRASAD (Seed Research, 2026)
To know the influence of pollen storage conditions and period on seed set, seed yield and quality of sunflower hybrid KBSH-1conducted at STR Unit, NSP, UAS Bangalore in two seasons Kharif 2001 and Rabi 2001-02. Pollen stored under refrigerated condition for 24 h gave highest seed set and seed yield followed by pollen stored in an earthen pot placed in a tray containing water. The seed quality in terms of 100 seed weight and vigour index were found significant due to storage period and conditions, while germination was non significant.